Retraction notice to “Company financial path analysis using fuzzy c-means and its application in financial failure prediction” [Journal of Business Economics and Management, 19(1), 213-234, 2018] - Liu, Jiaming; Wu, Chong (Journal of Business Economics and Management, 2018)
The following article will be retracted from publication in Journal of Business Economics and Management:Company financial path analysis using fuzzy c-means and its application in financial failure prediction by Jiaming Liu and Chong Wu, Volume 19, Issue 1, pp. 213-234, Journal of Business Economics and Management, 2018, https://doi.org/10.3846/16111699.2017.1415959 https://journals.vgtu.lt/index.php/JBEM/article/view/1606Received 17 September 2017, accepted 7 December 2017,since there are presented some paraphrased ideas with slight changes from published articlePredicting corporate bankruptcy using a self-organizing map: An empirical study to improve the forecasting horizon of a financial failure model, by Philippe du Jardin and Eric Séverin, Volume 51, Issue 3, pp. 701-711, Decision Support Systems, 2011, https://doi.org/10.1016/j.dss.2011.04.001Received 15 September 2010, accepted 11 April 2011.The Editors and publishers of the journal, Vilnius Gediminas Technical University, note that we received, peer-reviewed, accepted and published the article on the basis that the authors are presenting original results.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “retracted”.